Pengaruh Dimensi Service Quality Terhadap Kepuasan Pasien di Bagian Rawat Inap Rumah Sakit Immanuel Bandung - Albert Iskandar; Agustinus Februadi (Majalah Ilmiah UNIKOM, 2021)
The purpose of this study was to determine impact from each dimension of Parasuraman Service Quality on Patient Satisfaction in Patient Unit Immanuel Hospital. The population of this study is Patient Unit users in Immanuel Hospital period April to May 2021. The sampling used Purposive Sampling Method with total sample 150. PLS-SEM with SmartPLS v. 3.2.9 is used as a tool for data analysis. The results showed that Empathy Dimension have most effect on Patient Satisfaction, and others dimension has no effect on Patient Satisfaction. Key Words : Service Quality, Customer Satisfaction, Structural Equation Modelling, Path Analysis